2012
DOI: 10.3746/pnf.2012.17.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Extract from Edible Red Seaweed (Gelidium amansii) Inhibits Lipid Accumulation and ROS Production during Differentiation in 3T3-L1 Cells

Abstract: Gelidium (G.) amansii is a red alga widely distributed in the shallow waters around East Asian countries. We investigated the effect of G. amansii on lipid accumulation and ROS (Reactive Oxygen Species) production in 3T3-L1 cells. G. amansii extracts dose-dependently inhibited lipid formation and ROS generation in cultured cells. Our results showed that anti-adipogenic effect of G. amansii was due to the reduction in mRNA expressions of PPARγ peroxisome proliferator-activated receptor-γ and aP2 (adipocyte prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Moreover, GAE attenuated H/R-mediated increase of BAX and caspase 3 expressions while promoting Bcl-2 expression, indicating that GAE helps maintain a balance between proapoptotic and antiapoptotic proteins. A previous report demonstrating that G. amansii extract suppresses ROS production, and protects against oxidative stress by activating ROS-scavenging enzymes in 3T3-L1 cells [20], also suggests that antioxidant property might contribute, at least in part, to GAE-mediated neuroprotection in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, GAE attenuated H/R-mediated increase of BAX and caspase 3 expressions while promoting Bcl-2 expression, indicating that GAE helps maintain a balance between proapoptotic and antiapoptotic proteins. A previous report demonstrating that G. amansii extract suppresses ROS production, and protects against oxidative stress by activating ROS-scavenging enzymes in 3T3-L1 cells [20], also suggests that antioxidant property might contribute, at least in part, to GAE-mediated neuroprotection in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, GAE significantly suppressed ROS accumulation in cultured neurons as opposed to the amount of ROS in untreated neurons and successfully attenuated these pathological consequences. A previous report demonstrating that G. amansii extract suppresses ROS production, and protects against oxidative stress by activating ROS-scavenging enzymes in 3T3-L1 cells [19] also supports that antioxidant property might contribute, at least in part, to GAE-mediated neuroprotection in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Among the seaweeds, recently, red seaweeds were shown to have anti-obesity effects [25,26]. In previous studies, it was revealed that an ethanol extract prepared from red seaweed exerted anti-adipogenic activities in 3T3-L1 adipocytes [25,26,38,39]. Therefore, this study investigated the anti-obesity effects of G. elliptica 60% ethanol extract (GEE) in high-fat diet (HFD)-induced obese mice.…”
Section: Introductionmentioning
confidence: 98%